Case Report of Transformation from Multiple Myeloma IgG KAPPA to Primary Plasma Cell Leukemia - Aguilar, Sandra Ivette López; Espinosa, Luis Daniel Solorzano; Calvillo, David Sebastián Ramírez; Montiel, Oscar Rame; Carbajal, Any Yareli Diaz (British Journal of Healthcare and Medical Research, 2025)
-